2016
DOI: 10.1016/j.joca.2016.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Nociceptive phenotype alterations of dorsal root ganglia neurons innervating the subchondral bone in osteoarthritic rat knee joints

Abstract: Up-regulation of nociceptive markers in subchondral bone afferents correlated with subchondral bone damage, suggesting that subchondral bone is a therapeutic target, especially in the case of advanced stage knee OA. In particular, CGRP and TrkA are potentially molecular therapeutic targets to treat joint pain associated with subchondral lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 38 publications
1
33
2
Order By: Relevance
“…NGF‐immunoreactive cells were colocalized with sensory nerve fibers within osteochondral channels in human subchondral bone . Indeed, most sensory neurons innervating the subchondral bone in rat knee joints were found to be TrkA‐immunoreactive , and TrkA expression in subchondral bone afferents was further increased during mono‐iodoacetate–induced OA in rats .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…NGF‐immunoreactive cells were colocalized with sensory nerve fibers within osteochondral channels in human subchondral bone . Indeed, most sensory neurons innervating the subchondral bone in rat knee joints were found to be TrkA‐immunoreactive , and TrkA expression in subchondral bone afferents was further increased during mono‐iodoacetate–induced OA in rats .…”
Section: Discussionmentioning
confidence: 97%
“…Microarray analysis of BMLs in OA demonstrated up‐regulation of genes implicated in neurogenesis, osteochondral turnover, and inflammation that might contribute to OA pain . In animals, OA caused up‐regulation of nociceptive markers (calcitonin gene‐related peptide and tropomyosin receptor kinase A [TrkA]) in subchondral bone afferents . However, the mechanisms by which subchondral pathology contributes to OA pain are incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…In light of the side effect profile of NSAIDs and opiates, new mechanism‐based analgesics that relieve bone pain with a lower side effect profile are clearly needed. To develop such analgesics, rodent models of malignant and nonmalignant bone pain were developed . These models of bone pain were then utilized to define the mechanisms that drive bone pain, test whether new mechanism‐based therapies could relieve bone pain and translate promising candidates into human clinical trials .…”
Section: Introductionmentioning
confidence: 99%
“…This is in line with accelerated subchondral bone loss, but so far no such observations have been reported for other OA joints [50]. The subchondral bone of rat knee joints with monoiodacetate-induced OA showed clear sprouting of CGRP- and tropomyosin receptor kinase A (TrkA)-immunoreactive fibers and this phenomenon was associated with increased pain [51] (Figure 1). Interestingly, Ghilardi et al demonstrated that in a mouse model of chronic arthritic pain induced by Complete Freund Adjuvant (CFA) injection into the knee joint, the sprouting of CGRP-positive sensory fibers in the synovium is accompanied by sprouting of TH-positive sympathetic fibers in close proximity [52].…”
Section: Sensory and Sympathetic Nerve Fibers In Osteoarthritic Jomentioning
confidence: 57%